Technology transfer as technological learning: a source of competitive advantage for firms with limited R&D resources - Lin, Bou-Wen (R & D management, 2003)
The objective of this article is to answer why and how firms in developing countries with limited R&D resources can gain sustainable competitive advantage through technology transfer (TT). Successful firms are those that can accumulate competence through internal technological learning after transferring technologies from external technology sources. Organizational intelligence, firm specificity of technology, and causal ambiguity are identified as three mediators between technological learning performance and several antecedents previously discussed in the literature. A survey of Taiwanese manufacturers is conducted to explore the technological learning phenomenon as an integral part of TT, which is important but often neglected. This article also provides an interesting research setting for the evaluation of technological learning theories.